PENGEMBANGAN PERANGKAT PEMBELAJARAN MATEMATIKA DENGAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING BERBASIS PEMBELAJARAN BERDIFERENSIASI PADA MATERI DERET ARITMATIKA KELAS X SMA - Triyanti, Yeni; Hanifah, Hanifah; Sumardi, Hari (LPPM Universitas Bina Bangsa, 2024)
This research is development research which aims to produce valid and practical learning tools, namely RPP and Student Activity Sheets (LKPD) on arithmetic series material for class X SMA. This research began with an initial investigation analyzing the problems encountered at school. namely regarding the problems that occur in class X with mathematics learning, it is found that learning outcomes and students' active role in learning mathematics is still low. In this class the Merdeka curriculum has been implemented but differentiation learning has not been tried. The development model used is the plomp development model which consists of 5 stages, namely preliminary investigation, design, relations/construction (realization/construction), test, evaluation and revision (test, evaluation and revision) and implementation (implementation). Based on the results of data analysis, it was concluded that the mathematics learning tool using the PBL model was valid. RPP validation results 97%, LKPD 94% with very valid category. This means that the learning tools developed can be tested. Practical learning tools in small group trials with an average student response of 80% in the practical category